L2 stress discrimination by non-musicians and musicians playing wind or percussion instruments - Sandra Schwab; Orianne Pythoud (Langue(s) & Parole)
The present study explores the influence of music expertise on French-speaking listeners' ability to process L2 Spanish stress. Musicians playing wind or percussion instruments and non-musicians completed an Odd-One-Out task, where they heard three Spanish words presented in babble noise and were asked to detect the word with a different stress pattern. Results first showed that musicians (playing either wind or percussion instruments) outperformed non-musicians, confirming the advantage of music expertise in 'speech in noise' perception. Secondly, they revealed that percussionists – who, as rhythm experts, relied more on stress-related timing cues – performed better than musicians playing wind instruments – who, as pitch experts, were more sensitive to stress-related pitch cues – in detecting stress in Spanish words presented in babble noise. Finally, there was no evidence of the larger advantage of being a musician when processing L2 stress under perceptually challenging conditions. Taken together, our findings not only highlighted the benefits of music expertise in L2 stress perception, but also revealed that the type of music instruments played by the musicians also influences L2 stress discrimination performance.